Chrysin increased progesterone and LH levels, estrous phase duration and altered uterine histology without affecting aromatase expression in rat ovary. (February 2022) - Abbas, Manal A.; Alqaisi, Khalid M.; Disi, Ahmad; Hameed, Naghm A.
Graphical abstract: Highlights: Chrysin increased serum LH and progesterone levels. Chrysin produced histological alterations in the uterus. Chrysin had no effect on aromatase expression in the ovary. Chrysin had no effect on progesterone or estrogen receptor alpha expression in the uterus. Abstract: The effect of chrysin, a flavonoid found in Passiflora spp ., honey and propolis on female sex hormones and on ovarian and uterine histology was studied. Treatment of Wistar rats with chrysin (100 mg/kg) for 28 days resulted in persistent or prolonged estrous phase. Histologically, no difference was found between different groups in the percentage of atretic preantral and antral follicles. Uteri of chrysin-treated groups had slit-like lumens during the estrous stage compared to the control group that had fluid-filled wide lumens. The height of luminal epithelium was higher in chrysin-treated groups and had more apoptotic cells. Immunohistochemical studies showed that chrysin had no effect on aromatase expression in the ovary or progesterone and estrogen-receptor alpha expression in the uterus. LH and progesterone, but not estrogen and FSH, levels were higher in chrysin-treated group. In conclusion, chrysin increased LH and progesterone levels and produced histological alterations in the uterus.